Restraint and handling of wild and domestic animals - Fowler, Murray E. (Wiley-Blackwell, 2008)
New edition of the classic reference * Introduction to basic principles of animal restraint and overview of techniques * Focuses on the most effective physical restraint techniques * Provides essential information for ensuring the safety of both the handler and animal * Now in full color with five new chapters